OP0011 Construction of a physical map and identification of candidate genes for familial chondrocalcinosis at chromosome 5p15. (1st June 2001) - Pendleton, A; Wright, GD; Doherty, MD; Shiang, R; Hughes, A
Abstract : Background: A gene for familial chondrocalcinosis was previously mapped to a locus (CCAL2) on chromosome 5p. 1 The purpose of the study was to identify this gene and investigate its role in the pathogenesis of calcium pyrophosphate arthropathy and osteoarthritis. Objectives: Methods: A combination of physical cloning and candidate gene approach were employed to define CCAL2. Novel expressed sequence tags (ESTs) with expression in cartilage and which mapped to the critical region were identified from EST databases of GenBank. PCR generated DNA fragments from ESTs were radiolabelled using radioactive phosphorus and used as probes in Southern blot hybridization of high density plasmid artificial chromosome (PAC) filters. PACs were identified following autoradiography of the hybridisation membranes and the selected PACs were supplied by the UK HGMP resource centre in Cambridge. The Online Mendelian Inheritance in Man OMIM cytogenetic map was used to identify possible candidate genes within or near the critical region. Results: Six novel ESTs with high cartilage expression, identified 55 PACs following Southern blot hybridization. End sequencing of the PACs allowed the construction of a contig containing 25 PACs across the critical region. Two candidate genes were identified form OMIM. The first gene TRIO codes for a transmembrane multidomain protein which promotes the exchange of GDP for GTP in the extracellular matrix. An abnormality in this pathway is likely to produce an increase in extracellular triphosphate, which has a key role in inorganic pyrophosphate metabolism. The second gene ANK has only recently been mapped to the same location and it is responsible for articular calcification with associated arthritis in mice. Conclusion: The CCAL2 region has been physically mapped and two strong candidate genes are being screened for possible disease causing mutations. This gene should provide a greater understanding of pyrophosphate metabolism and of osteoarthritis with which there is a common association. Reference: Hughes AE, McGibbon D, Woodward E, Dixey J, Doherty M. Hum Mol Genet. 1995;4 :1225–8